Creative Calligraphy - Halliday, Peter, 1939- (London BCA., 1991)
Shows how to do various types of lettering using crayons and felt tipped pens rather than special equipment, and how to make cards, posters, mobiles and word pictures. Suggested level: intermediate, junior secondary.
Include Index and Illustrations
Keywords: Calligraphy